2013
DOI: 10.3389/fnbot.2013.00020
|View full text |Cite
|
Sign up to set email alerts
|

Robust active binocular vision through intrinsically motivated learning

Abstract: The efficient coding hypothesis posits that sensory systems of animals strive to encode sensory signals efficiently by taking into account the redundancies in them. This principle has been very successful in explaining response properties of visual sensory neurons as adaptations to the statistics of natural images. Recently, we have begun to extend the efficient coding hypothesis to active perception through a form of intrinsically motivated learning: a sensory model learns an efficient code for the sensory si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…In contrast to the relative scarcity of research into infant curiosity, recent years have seen a surge in interest in the role of intrinsic motivation in autonomous computational systems. Equipping artificial learning systems with intrinsic motivation mechanisms is likely to be key to building autonomously intelligent systems (Baranes & Oudeyer, ; Oudeyer, Kaplan, & Hafner, ), and consequently a rapidly expanding body of computational and robotic work now focuses on the intrinsic motivation mechanisms that may underlie a range of behaviors; for example, low‐level perceptual encoding (Lonini et al., ; Schlesinger & Amso, ), novelty detection (Marsland, Nehmzow, & Shapiro, ), and motion planning (Frank, Leitner, Stollenga, Förster, & Schmidhuber, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the relative scarcity of research into infant curiosity, recent years have seen a surge in interest in the role of intrinsic motivation in autonomous computational systems. Equipping artificial learning systems with intrinsic motivation mechanisms is likely to be key to building autonomously intelligent systems (Baranes & Oudeyer, ; Oudeyer, Kaplan, & Hafner, ), and consequently a rapidly expanding body of computational and robotic work now focuses on the intrinsic motivation mechanisms that may underlie a range of behaviors; for example, low‐level perceptual encoding (Lonini et al., ; Schlesinger & Amso, ), novelty detection (Marsland, Nehmzow, & Shapiro, ), and motion planning (Frank, Leitner, Stollenga, Förster, & Schmidhuber, ).…”
Section: Introductionmentioning
confidence: 99%
“…In that regard, one essential property of our model is that it is fully self-calibrating. In an analysis of the vergence model in [18], Lonini et al showed that the model can adapt to different kind of perturbations such as blur, or eye misalignments [21] [22]. This property is an important step towards autonomous robots capable of open ended learning.…”
Section: Resultsmentioning
confidence: 96%
“…Our model includes inputs from both foveal and peripheral regions of the retinae (Lonini et al, 2013). The fovea is assumed to be a square region subtending 7 degrees of visual angle and centered on the optical axis.…”
Section: Developmental Model Of the Optokinetic Reflexmentioning
confidence: 99%